2016
DOI: 10.21276/ijmrp.2016.2.6.028
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Associated Factors of Generalized Anxiety Disorder Among Physicians, Jeddah, Saudi Arabia

Abstract: Background: Generalized anxiety disorder (GAD) is one of the most common mental disorders in primary care settings and is associated with increased use of health services. Patients with GAD demonstrate a considerable degree of impairment and disability, even in its pure form, uncomplicated by depression or other mental disorders. Objectives: To explore the magnitude of the problem of anxiety disorders among physicians working in general governmental hospitals in Jeddah and its determinants. Subjects and Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
0
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
2
0
0
Order By: Relevance
“…The first study was carried out at the very early phase of the COVID-19 pandemic where the total COVID-19 cases were lower than 1000, while the latter study (not yet peer-reviewed) was carried out at the similar phase of the present study where the exponential growth in the number of cases was initiated. However, the prevalence was within the range of that reported by studies among the various population within Saudi Arabia (prevalence varied 15.8%–26% for depression and 16.6%–66% for anxiety) before the COVID-19 outbreak [ [28] , [29] , [30] , [31] , [32] ]. A similar or higher prevalence of psychological burden was reported during the past major infectious diseases outbreaks, such as MERS, SARS and Ebola, especially among those directly affected by the outbreaks [ [9] , [10] , [11] , 13 , 33 ].…”
Section: Discussionsupporting
confidence: 70%
“…The first study was carried out at the very early phase of the COVID-19 pandemic where the total COVID-19 cases were lower than 1000, while the latter study (not yet peer-reviewed) was carried out at the similar phase of the present study where the exponential growth in the number of cases was initiated. However, the prevalence was within the range of that reported by studies among the various population within Saudi Arabia (prevalence varied 15.8%–26% for depression and 16.6%–66% for anxiety) before the COVID-19 outbreak [ [28] , [29] , [30] , [31] , [32] ]. A similar or higher prevalence of psychological burden was reported during the past major infectious diseases outbreaks, such as MERS, SARS and Ebola, especially among those directly affected by the outbreaks [ [9] , [10] , [11] , 13 , 33 ].…”
Section: Discussionsupporting
confidence: 70%
“…The prevalence of anxiety and depression disorders among the general public was higher than that reported by a study conducted during the same period in the Kingdom (Alyami et al, 2020). However, the prevalence was within the range of that reported by studies among the various population within Saudi Arabia (prevalence varied 15.8% to 26% for depression and 16.6% to 66% for anxiety) before the COVID-19 outbreak (Al-Qadhi et al, 2014; Alzahrani et al, 2016; Alanazy, 2019; Alharithy et al, 2019; Al Salman et al, 2020). A similar or higher prevalence of psychological burden was reported during the past major infectious diseases outbreaks, such as MERS, SARS and Ebola, especially among those directly affected by the outbreaks (Mak et al, 2010; Alnajjar et al, 2016; Jalloh et al, 2018; Cabello et al, 2020; Brooks et al, 2020).…”
Section: Discussionsupporting
confidence: 69%
“…Another study done on resident physicians in 2020 at King Fahad Medi-cal City (KFMC), Riyadh, showed the prevalence of depression among family medicine doctors was 18.5% [4]. Additionally, in a study that was done in Jeddah governmental hospitals, 13% were found to have anxiety [5].…”
Section: Introductionmentioning
confidence: 99%